Certiorari and Interlocutory Judgments in Peru - Mundaca Rodríguez, Dalgir Katherine (2025)
The objective of this research is to analyze the feasibility of implementing certiorari in the national legal system, evaluate the discretionary criteria used in interlocutory judgments, and propose solutions that guarantee the protection of fundamental rights, especially in light of judges' discretionary power to decide whether or not to hear a case. To this end, a doctrinal and jurisprudential analysis methodology has been used. The importance of certiorari as a mechanism that allows the Supreme Court and the Constitutional Court to select cases of constitutional or legal relevance, thus optimizing their jurisdictional functions, is highlighted. Although this concept has been developed mainly in common law systems, it’s possible application in a civil law system, such as Peru's, has generated doctrinal debate. Nevertheless, its implementation could contribute to strengthening the institutional role of the higher courts, allowing for a more rational use of resources, guaranteeing respect for procedural principles, promoting the speed and predictability of proceedings, and significantly reducing the procedural burden.